2019
DOI: 10.1021/acs.iecr.9b02211
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Hydrogen Peroxide over Au–Pd Supported Nanoparticles under Ambient Conditions

Abstract: The direct synthesis of hydrogen peroxide (H 2 O 2 ) from molecular H 2 and O 2 over Au−Pd/TiO 2 catalysts prepared using a modified impregnation methodology is studied. Initially we investigated the role of the Au:Pd ratio on the catalytic activity toward H 2 O 2 formation and its subsequent degradation under conditions that have previously been found to be optimal for the formation of H 2 O 2 using high pressure reactants and low temperatures. Subsequently, we have conducted a detailed study of H 2 O 2 synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 59 publications
9
66
0
Order By: Relevance
“…The modification of Pd via the addition of a range of secondary, non-precious metals has previously been demonstrated to enhance catalytic selectivity, with a reduction in the amount of contiguous Pd ensemble sites and an enhancement in the number of isolated Pd sites often reported as the cause for the improvement in catalytic selectivity towards H 2 O 2 . 35 In keeping with these studies, we now report the For any catalyst operating in a three-phase system the possibility of leaching of the active phase is of great concern, with the low stability of sol-immobilized catalysts well known. 36 Indeed previous work by Dissanayake and Lunsford has demonstrated the high activity of homogeneous Pd species in the direct synthesis of H 2 O 2 .…”
Section: Catalyst Evaluation For the Direct Synthesis Of H 2 Omentioning
confidence: 77%
“…The modification of Pd via the addition of a range of secondary, non-precious metals has previously been demonstrated to enhance catalytic selectivity, with a reduction in the amount of contiguous Pd ensemble sites and an enhancement in the number of isolated Pd sites often reported as the cause for the improvement in catalytic selectivity towards H 2 O 2 . 35 In keeping with these studies, we now report the For any catalyst operating in a three-phase system the possibility of leaching of the active phase is of great concern, with the low stability of sol-immobilized catalysts well known. 36 Indeed previous work by Dissanayake and Lunsford has demonstrated the high activity of homogeneous Pd species in the direct synthesis of H 2 O 2 .…”
Section: Catalyst Evaluation For the Direct Synthesis Of H 2 Omentioning
confidence: 77%
“…3). While numerous studies have reported the beneficial effect of sub-ambient temperatures on the direct synthesis of H 2 O 2, owing to an inhibition of H 2 O 2 degradation pathways [15,29], typically temperatures exceeding 140 °C have been explored for the oxidation of cyclohexane under aerobic conditions [30] as such a large conditions gap exists between the two key reaction steps. Temperatures between 50 and 140 °C were evaluated for cyclohexane oxidation via the in-situ production of H 2 O 2 , with the results shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While Pd-based catalysts have been well reported to offer high activity towards H 2 O 2 production via the direct route [1,3,[10][11][12][13][14], there has been extensive investigation into the alloying of Pd with secondary metals to improve catalytic performance [15][16][17][18][19][20][21][22][23][24]. Indeed, the introduction of Au into supported Pd catalysts has been widely demonstrated to improve catalytic efficacy, with electronic, structural and isolation effects all potential causes for the enhanced performance typically observed in AuPd bi-metallic systems [25][26][27][28]. Indeed we have previoulsy reported the ability of Au to promote the catalytic performance of Pd-based catalysts over a range of reaction conditions [28].…”
Section: Introductionmentioning
confidence: 99%